COMPLEX DYNAMIC SYSTEMS THEORY IN LANGUAGE LEARNING: A SCOPING REVIEW OF 25 YEARS OF RESEARCH - Hiver, Phil; Al-Hoorie, Ali H.; Evans, Reid (Studies in second language acquisition, 2022)
A quarter of a century has passed since complex dynamic systems theory was proposed as an alternative paradigm to rethink and reexamine some of the main questions and phenomena in applied linguistics and language learning. In this article, we report a scoping review of the heterogenous body of research adopting this framework. We analyzed 158 reports satisfying our inclusion criteria (89 journal articles and 69 dissertations) for methodological characteristics and substantive contributions. We first highlight methodological trends in the report pool using a framework for dynamic method integration at the levels of study aim, unit of analysis, and choice of method. We then survey the main substantive contribution this body of research has made to the field. Finally, examination of study quality in these reports revealed a number of potential areas of improvement. We synthesize these insights in what we call the “nine tenets” of complex dynamic systems theory research, which we hope will help enhance the methodological rigor and the substantive contribution of future research.